2019
DOI: 10.1021/acs.energyfuels.8b04268
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Viscosity Measurements of a Cyclopentane Hydrate Slurry in Waxy Water-in-Oil Emulsions

Abstract: With the tendency of the offshore petroleum industry moving to the deep-water fields, there are several challenges for the exploration and development of oil and gas with higher paraffin content in the deep-water severe environment, especially the complex flow assurance issues including the coexistence of wax precipitation and hydrate formation. The effects of wax on hydrate slurry viscosity, hydrate nucleation and growth, and hydrate dissociation were investigated in a rheometer. Results indicated that the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…Up to now, many studies have been conducted to investigate the interaction between hydrate and wax in terms of nucleation, formation, agglomeration, , deposition, , and plugging . The details and main conclusions of these studies have been discussed in our previous study and will not be repeated here.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many studies have been conducted to investigate the interaction between hydrate and wax in terms of nucleation, formation, agglomeration, , deposition, , and plugging . The details and main conclusions of these studies have been discussed in our previous study and will not be repeated here.…”
Section: Introductionmentioning
confidence: 99%
“…While l -l is an amino acid hydrate surfactant, Liu et al 28 found that l -l was a good promoter for the bubble-free hydrate decomposition; although its hydrate promotion effect is slightly lower than that of SDS, l -l decomposition is bubble-free and eco-friendly, and the promotion mechanism of amino acid surfactant is different from that of SDS. Chen et al 29 believed that compared with the pure water system, the l -l system had significantly shorter hydrate formation time and faster growth rate; a comparison on the change of l -l molecule position and the hydrate formation system potential energy was performed, l -l tended to adsorb on the gas–liquid interface and hydrate surface, and disturbance was formed on the gas–liquid interface-hydrate surface – gas–liquid interface, which was shown as the rise of system potential energy, and then the potential energy dropped sharply until the completion of hydrate layer growth, further demonstrating the positive effect of surface adsorption on methane hydrate formation. Therefore, its mechanism of promotion is quite different from that of SDS.…”
Section: Resultsmentioning
confidence: 99%
“…To date, different research has been performed to study the coupling between hydrate issues and wax issues. The results of this research haves shown that wax could affect hydrate issues through affecting the nucleation, formation, agglomeration, , deposition, , and plugging processes. However, the main conclusions and mechanisms obtained from this research can be quite different and sometimes contradictory with each other.…”
Section: Introductionmentioning
confidence: 84%